2005
DOI: 10.1080/10428190500102662
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation complicating acute lymphoblastic leukemia: A study of childhood and adult cases

Abstract: A high incidence of disseminated intravascular coagulation (DIC) in adult patients with acute lymphoblastic leukemia (ALL) is reported. However, studies comprising both childhood and adult patients are sparse and the clinical relevance of DIC in ALL patients has been a conflicting issue. Coagulation profiles at presentation and within seven days after starting remission-induction therapy of 44 childhood and 51 adult ALL patients were studied. At presentation, two childhood (5%) and 11 adult (22%) patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…We discovered 11 patients with SIL-TAL1 developing overt DIC in different degrees according to the scoring system given by International Society on Thrombosis and Hemostasis (ISTH). In previous literatures, the DIC was found in about 10% of adult ALL patients, and less than 5% in childhood ALL [25], [26]. In our study, the incidence of DIC was much higher in patients carrying SIL-TAL1 , and most DIC accompanying with TLS occurred in the early stage of induction therapy, which indicated that DIC may also be related to the breaking down of leukemia cells during chemotherapy.…”
Section: Discussionsupporting
confidence: 56%
“…We discovered 11 patients with SIL-TAL1 developing overt DIC in different degrees according to the scoring system given by International Society on Thrombosis and Hemostasis (ISTH). In previous literatures, the DIC was found in about 10% of adult ALL patients, and less than 5% in childhood ALL [25], [26]. In our study, the incidence of DIC was much higher in patients carrying SIL-TAL1 , and most DIC accompanying with TLS occurred in the early stage of induction therapy, which indicated that DIC may also be related to the breaking down of leukemia cells during chemotherapy.…”
Section: Discussionsupporting
confidence: 56%
“…The incidence of DIC in this report was probably underestimated as paediatric ICU and emergency care patients were not included 1. The incidence of DIC in childhood acute lymphoblastic leukaemia and acute promyelocytic leukaemia (APML) were reported as 14%11 and 4%–8%,12 respectively.…”
Section: Aetiological Factors For Dicmentioning
confidence: 75%
“…When available, data refer mostly to patients symptomatic for bleeding or thrombosis, and diagnostic criteria are largely heterogeneous (Table 1). 9,10,[26][27][28] These studies show that clinically overt DIC may be diagnosed in $15% of patients with acute leukemia, with a tendency to higher figures in AML than in ALL, and in adult patients than in children. Higher rates of patients show clinical and/or laboratory findings of DIC after starting treatment, consistent with the release of procoagulants and cytokines by leukemic cells damaged by chemotherapy.…”
Section: Clinical Impact and Manifestations Of Dic In Hematologic Malmentioning
confidence: 85%